Network connectedness in vertical and horizontal manufacturing joint venture formations: A power perspective. Issue 2 (March 2017) - Carnovale, Steven; Yeniyurt, Sengun; Rogers, Dale S.
Abstract: In the supply chain management (SCM) domain, research has been advanced to understand the role of network structure in buyer-supplier relations. Yet, while there has been a substantial body of work investigating supply chain networks, little research has paid attention to how the network structure affects the power balance between manufacturers and suppliers. This study investigates, from a power perspective, the role that network connectedness plays in new equity based joint venture formations. As such, we further the understanding of supply chain networks by examining network structure as a mechanism from which firms derive power. We articulate several hypotheses rooted in both network and power theories by specifically examining, from a power perspective, factors such as eigenvector centrality, closeness centrality, and weak components centrality. Further, we differentiate between horizontal and vertical joint venture configurations and elucidate the moderating effect it has in engendering new manufacturing joint venture formations. Empirical results show that structural network based power is a significant explanatory mechanism in new joint venture formation, and specifically, that power is, and should be a primary consideration in supply chain partnership decisions. Highlights: Examines the role of structural network power in manufacturing joint venture formations. Eigenvector centrality, closeness centrality and weak components centrality are examined. Differentiates between horizontal and vertical JV power configurations. Results suggest that structural network power is a significant explanatory mechanism in new JV formation.